Catalytic Oxidation of Benzene Using Mesoporous alpha-Mn2O3 - An, Hyung Bum; Kim, Ji Man; Jurng, Jongsoo; Bae, Gwi-Nam; Jeon, Jong-Ki; Park, Sung Hoon; Park, Young-Kwon (AMER SCIENTIFIC PUBLISHERS, 2013)
The catalytic oxidation of benzene was carried out over mesoporous alpha-Mn2O3, MnOx/KIT-6, and bulk commercial Mn oxides (Mn2O3, MnO2, and MnO). The catalysts were characterized using X-ray diffraction, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis, and temperature-programmed reduction analysis. MnOx/KIT-6, prepared by impregnating MnOx on KIT-6, exhibited a low activity for the oxidation of benzene, whereas mesoporous alpha-Mn2O3, manufactured using KIT-6 as the template, showed a high activity. The order of the activities of bulk Mn oxides for benzene decomposition was shown to be Mn2O3 > MnO2 > MnO. Therefore, the high activity of mesoporous alpha-Mn2O3 is attributed to the uniform distribution of highly active Mn2O3 in the mesoporous structure.
Keywords: LOW-TEMPERATURE; OZONE; TOLUENE